High arsenic contamination in drinking water hand-pumps in Khap Tola, West Champaran, Bihar, India - Bhatia, Siddharth; Balamurugan, Guru; Baranwal, Annu (Frontiers in Environmental Science, 2014)
This study tests the drinking water supply of a marginalized village community of Khap Tola in the state of Bihar, a state in Northern India. Based on hand pump drinking water sample testing and analysis, we found that there was high levels of arsenic (maximum value being 397 ppb) , in excess of the WHO limits of 10ppb. Analysis showed 57% of the samples from private hand-pumps in the shallow aquifer zone of 15-35m have arsenic greater than 200 ppb. Using GIS overlay analysis technique it was calculated that 25% of the residential area in the village is under high risk of arsenic contamination. Further using USEPA guidelines, it was calculated that children age group 5-10 years are under high risk of getting cancer. The Hazard Quotient calculated for 21 children taken for study, indicated that children may have adverse non-carcinogenic health impacts, in the future, with continued exposure. Since the area adds a new arsenic contaminated place in India, further geochemical analysis and health assessment needs to be done in this district of West Champaran in, Bihar.